2017
DOI: 10.1002/jcp.25663
|View full text |Cite
|
Sign up to set email alerts
|

Polydeoxyribonucleotides (PDRNs) From Skin to Musculoskeletal Tissue Regeneration via Adenosine A2A Receptor Involvement

Abstract: Polydeoxyribonucleotides (PDRNs) are low molecular weight DNA molecules of natural origin that stimulate cell migration and growth, extracellular matrix (ECM) protein production, and reduce inflammation. Most preclinical and clinical studies on tissue regeneration with PDRNs focused on skin, and only few are about musculoskeletal tissues. Starting from an overview on skin regeneration studies, through the analysis of in vitro, in vivo, and clinical studies (1990-2016), the present review aimed at defining the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 50 publications
0
36
0
Order By: Relevance
“…Polydeoxyribonucleotide (PDRN) is a mixture of nucleotides with molecular weights of 50-1500 kDa that originates from the human placenta or salmon sperm [17]. PDRN facilitates skin regeneration by activating adenosine A 2A receptor (A 2A R) [17]. A 2A R is involved in the anti-inflammatory pathway and in the VEGF production [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polydeoxyribonucleotide (PDRN) is a mixture of nucleotides with molecular weights of 50-1500 kDa that originates from the human placenta or salmon sperm [17]. PDRN facilitates skin regeneration by activating adenosine A 2A receptor (A 2A R) [17]. A 2A R is involved in the anti-inflammatory pathway and in the VEGF production [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…PDRN facilitates skin regeneration by activating adenosine A 2A receptor (A 2A R) [17]. A 2A R is involved in the anti-inflammatory pathway and in the VEGF production [17,18]. PDRN inhibits apoptosis and exerts anti-inflammatory effect by suppressing the production of inflammatory cytokines [12,18].…”
Section: Introductionmentioning
confidence: 99%
“…Effect of PDRN size on wound closure in mice skin. Multiple previous studies have demonstrated that PDRNs promote wound healing in various animal models (6,10,(18)(19)(20). To evaluate the effect of PDRNs on wound healing, 8-week old hairless (SKH1) mice were given different sizes of PDRNs daily for a week.…”
Section: Resultsmentioning
confidence: 99%
“…A number of previous studies have demonstrated that classic PDRN functions as a growth promoter in the regeneration of various tissues, including wounded skin, and in osteoarthritis and ischemic-reperfusion injuries (10,29,30). Based on the beneficial effects of PDRN, the effects of different molecular size DNA mixtures on wound healing were investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation